2021
DOI: 10.1161/jaha.121.021566
|View full text |Cite
|
Sign up to set email alerts
|

Research Priorities in the Secondary Prevention of Atrial Fibrillation: A National Heart, Lung, and Blood Institute Virtual Workshop Report

Abstract: There has been sustained focus on the secondary prevention of coronary heart disease and heart failure; yet, apart from stroke prevention, the evidence base for the secondary prevention of atrial fibrillation (AF) recurrence, AF progression, and AF‐related complications is modest. Although there are multiple observational studies, there are few large, robust, randomized trials providing definitive effective approaches for the secondary prevention of AF. Given the increasing incidence and prevalence of AF natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 121 publications
1
61
0
1
Order By: Relevance
“…Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, which results in a 4- to 5- fold increased risk for stroke, tripling of the risk for heart failure, and 40–90% higher risk for all-cause mortality ( 1 ). Previous studies have revealed multiple risk factors for AF, including older age, male sex, concomitant cardiovascular conditions, diabetes, and sleep apnea ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, which results in a 4- to 5- fold increased risk for stroke, tripling of the risk for heart failure, and 40–90% higher risk for all-cause mortality ( 1 ). Previous studies have revealed multiple risk factors for AF, including older age, male sex, concomitant cardiovascular conditions, diabetes, and sleep apnea ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acceptable and accurate technologies for pAF monitoring are needed. 43 Forty-five percent of stroke treatment costs are incurred from acute care and monitoring. 7 Pulsewatch offers a lower-cost monitor that would accelerate the diagnosis and treatment of pAF in elderly stroke patients, preventing further strokes and thus decreasing the overall cost of treating stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the success rate of a single operation is only 66.6% in paroxysmal AF [ 11 ]. Meanwhile, despite multifaceted efforts, prevention of AF remains challenging [ 12 ] and it is essential to investigate the correlation and mechanisms between potential modifiable risk factors and AF.…”
Section: Introductionmentioning
confidence: 99%